2018
DOI: 10.33301/jed-p-2018-20-02-03
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Analysis of Vietnam Bilateral Trade Efficiency

Abstract: This paper used a stochastic frontier gravity model to evaluate the bilateral trade efficiency of Vietnam using the bilateral trade data of Vietnam’s main trade counterparts in the period 2000- 2015. Trade efficiency means the actual trade in comparison with the trade potential. Empirical results show that Vietnam’s trade performance was significantly lower than the potential level. Joining the WTO did not improve trade efficiency. The impact of FTAs on exploiting bilateral trade potential is heterogeneous acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Vietnam—Korean Free Trade Agreement (VKFTA), Comprehensive and Progressive Agreement for Trans‐Pacific Partnership (CPTPP), Regional Comprehensive Economic Partnership (RCEP), European Union‐ Vietnam Free Trade Agreement (EVFTA)). Dinh Ho et al (2018) found that deep trade agreements appear to have limited impacts on Vietnam's trade efficiency, especially import side. In this study, we also consider the effect of deep trade agreements (DTAs) on facilitating technical NTMs imposed on Vietnamese agricultural imports.…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam—Korean Free Trade Agreement (VKFTA), Comprehensive and Progressive Agreement for Trans‐Pacific Partnership (CPTPP), Regional Comprehensive Economic Partnership (RCEP), European Union‐ Vietnam Free Trade Agreement (EVFTA)). Dinh Ho et al (2018) found that deep trade agreements appear to have limited impacts on Vietnam's trade efficiency, especially import side. In this study, we also consider the effect of deep trade agreements (DTAs) on facilitating technical NTMs imposed on Vietnamese agricultural imports.…”
Section: Introductionmentioning
confidence: 99%